[Information Package on "Accountability."] - National Education Association, Washington, DC.; National Education Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This document is an information package on accountability from the National Education Association (NEA). It is divided into three parts. Part one is a summary of the NEA conference on accountability, which made a number of unanimous recommendations for association action, including motions for program criteria, program evaluation, public information, and teacher training and certification. Part two is "Accountability," a speech by NEA executive secretary Terry Herndon, which advocates stopping the current destructive practices done in the name of accountability and encouraging good practices and good policy growing out of accountability phenomenon. Part three is composed of two large data sheets that present a survey of state activities on educational accountability derived from officials in state departments of education and state education associations. It is indicated that this document is as yet incomplete, presenting only a few details for each state, but it can serve as a composite of the state of the nation in accountability. (JA)
Availability: National Education Association, 1201 16th Street, N.W., Washington, D.C. (No price quoted).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Educational Practices; Evaluation Criteria; National Surveys; Program Effectiveness; Public Support; School Responsibility; Teacher Responsibility